Hubungan Kepatuhan Mengonsumsi Tablet Fe Dan Keteraturan Kunjungan ANC Dengan Kejadian Anemia Pada Ibu Hamil - Mariene Wiwin Dolang (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2020)
Objectives: The purpose of this study was to analyze the association of consuming Fe tablets and the regularity of ANC visits with the incidence of anemia in pregnant women in the health center passo the city of Ambon. Â Methods: The research design used in this study was analytic observational with a cross sectional study. The population is all pregnant women in the puskesmas working area pass the city from January to December 2017 using the total sampling technique. The sample in this study was 115 mothers.Â Results: The results showed the relationship between participation in consuming Fe tablets (p = 0,000) and regularity of ANC visits (p = 0.021) with the incidence of anemia in pregnant women at the health center passo in Ambon city.Â Conclusion: The conclusion in this study has to do with consuming Fe tablets and between the regularity of ANC visits and the incidence of anemia in pregnant women in the health center passo the city of Ambon. Needed for pregnant women to routinely carry out checks. Problems with anemia, special anemia can be detected and treated early.